Influence of odontogenic lesions on root development in impacted teeth: a cohort study - Barone, Selene; Antonelli, Alessandro; Madonna, Antonio; Greco, Vincenzo; Borelli, Massimo; Bennardo, Francesco; Giudice, Amerigo; Cevidanes, Lucia (Frontiers in Oral Health, 2025)
IntroductionRoot dilaceration, a clinically significant developmental anomaly that can complicate dental treatment, has been attributed to various etiological factors, but the role of odontogenic lesions is still poorly understood. This observational study aimed to evaluate the relationship between odontogenic lesions and root dilaceration in impacted teeth.MethodsThe sample size consisted of 22 impacted teeth divided into two groups: with odontogenic lesions (Group IwL) and without lesions (Group IwoL). Pre- and post-treatment radiographs, taken before and after conservative surgical or orthodontic-surgical management of impacted teeth, were used to assess the occurrence of dilaceration in both groups. Fisher's exact text was applied to compare the prevalence of dilaceration in both groups. In order to analyze the influence of each additional variable on dilaceration, a multivariate analysis was performed through logistic regression.ResultsRoot dilaceration was significantly more common in Group IwL (72.73%) than in Group IwoL (18.18%) (p = 0.030). No significant association was found between root dilaceration and additional variables, including impaction depth, cortical bone contact, maximum lesion size, and lesion volume.ConclusionsThis study provides novel evidence for a correlation between odontogenic lesions and root dilaceration, suggesting that compressive forces from these lesions may significantly contribute to abnormal root development, with important implications for clinical diagnosis and treatment planning.